Performance of Field-Collected Spodoptera frugiperda (Lepidoptera: Noctuidae) Strains Exposed to Different Transgenic and Refuge Maize Hybrids in Argentina. Issue 6 (16th December 2019) - Murúa, María G; Vera, Martín A; Michel, Andrew; Casmuz, Augusto S; Fatoretto, Julio; Gastaminza, Gerardo
Abstract: Spodoptera frugiperda (J. E. Smith) is one of the major pests of maize in Argentina. The main tool for its control is the use of genetically modified maize hybrids expressing Bacillus thuringiensis (Bt) insecticidal proteins. Maize growers in Argentina initially controlled this pest with Bt maize that expressed a single Bt protein (Cry1Ab or Cry1F). Currently it is necessary to plant maize cultivars that produce two Bt proteins to achieve the satisfactory control. Recently, Cry1F field-evolved resistant populations of this species were confirmed in Argentina. The objective of this study was to evaluate the performance of S. frugiperda field-collected strains on different Bt and non-Bt maize hybrids. Strains were collected from non-Bt maize (T1), Agrisure TDMax (T2), Agrisure Viptera (T3), Agrisure Viptera 3110 (T4), Genuity VT Triple Pro (T5), and Power Core (T6). Three experiments were performed to 1) determine the survivorship and reproduction of field-collected larvae (F0 ) from Bt maize hybrids, 2) evaluate Cry1F resistance using an F1 screen, and 3) assess the performance of F1 strains on different maize hybrids. In the F0, the survivorship from larva to adult ranged from 0 to 63%. We obtained adults from only the T1, T2, T5, and T6 strains with no significant differences in the reproductive parameters. Continuously rearing F1 larvae on their collected hosts affected larval duration, which was significantly shorter for a known-laboratory Bt-susceptible strain than the field-collected strains. Our results support the existence of Cry1F-resistance alleles in S. frugiperda field populations in Argentina.